OSL Dosimetry Using LiCaAlF\(_{6}\):Eu Phosphor (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
LiCaAlF\({}_{6}\):Eu (0.1 mol%) OSLD phosphor material in microcrystalline powder form was prepared in a two-step process. First, through co-precipitation method and second by quickly melting it in a graphite crucible at around 900\({}^{°}\)C. It is a very novel and economic method of preparing this phosphor. The formation of the material in a single phase was characterized by XRD. Optically stimulated luminescence (OSL) and photoluminescence studies were done for its application in radiation dosimetry of high-energy. The materials were irradiated to different doses of \(γ\)-rays using \({}^{60}\)Co radiation source and optically stimulated luminescence (OSL) decay curves were recorded. The powder material was found to be at least four times more sensitive than Al\({}_{2}\)O\({}_{3}\):C (Landauer USA) commercially available OSL chips. Considering these facts, the material could be considered as a highly sensitive and suitable OSL phosphor.
Keywords: LiCaAlF\({}_{6}\):Eu; Optically stimulated luminescence (OSL); High sensitivity; Dosimetry; OSLD phosphor